2020
DOI: 10.1177/1545968319887685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Robotic Path Assistance and Weight Support in Facilitating 3D Movements in Individuals With Poststroke Hemiparesis

Abstract: Background. High-intensity repetitive training is challenging to provide poststroke. Robotic approaches can facilitate such training by unweighting the limb and/or by improving trajectory control, but the extent to which these types of assistance are necessary is not known. Objective. The purpose of this study was to examine the extent to which robotic path assistance and/or weight support facilitate repetitive 3D movements in high functioning and low functioning subjects with poststroke arm motor impairment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…A recent study compared the effects of robotic path assistance and/or weight support on upper extremity kinematics among patients with stroke. [19] They showed that path assistance led to a faster movement in the high functioning group and that a combination of path assistance and weight support led to a smaller error in the low functioning group. However, path assistance was not superior to weight support alone with regard to upper extremity kinematics of especially the lower functioning group, when considering a trade-off between speed and error.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study compared the effects of robotic path assistance and/or weight support on upper extremity kinematics among patients with stroke. [19] They showed that path assistance led to a faster movement in the high functioning group and that a combination of path assistance and weight support led to a smaller error in the low functioning group. However, path assistance was not superior to weight support alone with regard to upper extremity kinematics of especially the lower functioning group, when considering a trade-off between speed and error.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, the kinematic analysis demonstrated that active-assistive robot training improves the smoothness but not the range of motion and straightness, indicating the subtle effects of active-assistive robot. A recent study compared the effects of robotic path assistance and/or weight support on upper extremity kinematics among patients with stroke [ 24 ]. They showed that path assistance led to a faster movement in the high functioning group and that a combination of path assistance and weight support led to a smaller error in the low functioning group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that long-duration intensive therapy can lead to clinically significant gains in function even in severely impaired patients with chronic stroke 26 . Several strategies can be implemented for these more severe patients including bimanual training 27 and weight-supported training 28 . If such strategies can be provided innovatively at home in high doses, the vicious cycle of paresis, immobility, muscle stiffness, and abnormal movement may be interrupted 29 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Several strategies can be implemented for these more severe patients including bimanual training 27 and weight-supported training. 28 If such strategies can be provided innovatively at home in high doses, the vicious cycle of paresis, immobility, muscle stiffness, and abnormal movement may be interrupted. 29 It has been shown that it is possible to achieve adaptability based on the patient's impairment level by selecting from several different devices that are integrated with a single rehabilitation platform.…”
Section: Discussionmentioning
confidence: 99%